INNOVATION MODEL OF ECONOMIC DEVELOPMENT OF UKRAINE - Bezchasniy, Leonid; Mel’nyk, Viktor (Journal of European Economy, 2018)
Conditions for implementation of objective laws of innovative economic growth in Ukraine are determined.